Minor variant detection in amplicons using 454 massive parallel pyrosequencing: experiences and considerations for successful applications. (September 2011) - Vandenbroucke, Ina; Van Marck, Herwig; Verhasselt, Peter; Thys, Kim; Mostmans, Wendy; Dumont, Stéphanie; Van Eygen, Veerle; Coen, Katrien; Tuefferd, Marianne; Aerssens, Jeroen
Ultra-deep sequencing (UDS) of amplicons is a major application for next-generation sequencing tech nologies, even more so for the 454 Genome Sequencer FLX. Especially for this application, errors that might be introduced during any of the sample processing or data analysis steps should be avoided or at least recognized, as they might lead to aberrant sequence variant calling. Since 454 pyrosequencing relies on PCR-driven target amplification, it is key to differentiate errors introduced during the amplification step from genuine minority variants. Thereto, optimal primer design is imperative because primer selection, primer dimer formation, and nonspecific binding may all affect the quality and outcome of amplicon-based deep sequencing. Also, other intrinsic PCR characteristics including amplification drift and the formation of secondary structures may influence sequencing data quality. We illustrate these phenomena using real life case studies and propose experimental and analytical evidence-based solutions for effective practice. Furthermore, because accuracy of the DNA polymerase is vital for reliable UDS results, a comparative analysis of error profiles from seven different DNA polymerases was performed and experimentally as-sessed in parallel by 454 sequencing. Finally, intra and interrun variability evaluation of the 454 sequencing protocol revealed highly reproducible results in amplicon-based UDS.